Hemoglobins, Hemorphins, and 11p15.5 Chromosomal Region in Cancer Biology and İmmunity with Special Emphasis for Brain Tumors - Altinoz, Meric Adil; Elmaci, Ilhan; Ince, Bahri; Ozpinar, Aysel; Sav, Aydin Murat (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
In systemic cancers, increased hemolysis leads to extracellular hemoglobin (HB), and experimental studies have shown its provoking role on tumor growth and metastasis. However, investigations have shown that HB chains presented by tumor vascular pericytes or serum protein complexes of HB could also induce antitumor immunity, which may be harnessed to treat refractory cancers and brain tumors. Mounting recent evidence shows that expression of HBs is not restricted to erythrocytes and that HBs exist in the cells of lung and kidney, in macrophages, and in neurons and glia of the central nervous system (CNS). HBs mediate coping with hypoxia and free radical stress in normal and tumor cells, and they are increased in certain tumors including breast, lung, colon, and squamous cell cancers. Recent studies showed HBs in meningioma, in the cyst fluid of craniopharyngioma, in the cerebrospinal fluid (CSF) of pediatric patients with posterior fossa tumors, and in glioblastoma cell lines. Hemorphins, abundant brain peptides formed via HB-chain cleavage, exert opioid activity and antiproliferative and immunomodifier effects. Hence mutations in HBs may modify brain tumorigenesis via influencing hemorphins and perturbing regulations of immune surveillance and cell growth in the neuroectodermal tissues. The β-globin gene cluster resides in the chromosome region 11p15.5, harboring important immunity genes and IGF2, H19, PHLDA2/TSSC3, TRIM3, and SLC22A18 genes associated with cancers and gliomas. 11p15.5 is a prominent region subject to epigenetic regulation. Thus the β-globin loci may exert haplotypal interactions with these. Some clues support this theory. It is well established that iron load induces liver cancer in thalassemia major; however iron load–independent associations also exist. Enhanced rates of hematologic malignancies are associated with HB Lepore, association of hemoglobin E with cholangiocarcinoma, and enhanced gastric cancer rates in the thalassemia trait. In the African Herero population, a mutant form of δ-globin is very prevalent, and this population has higher rates of pediatric brain tumors. Globins are also expressed in healthy endothelia and in tumoral vessels, indicating potential involvement in angiogenesis. Studies on HBs and their cleavage peptides in cancers and brain tumors may lead to innovative treatment strategies.
Keywords: hemoglobins; brain tumors; 11p15.5 gene cluster